Recent Advances of Osterix Transcription Factor in Osteoblast Differentiation and Bone Formation - Liu, Qian; Li, Mao; Wang, Shiyi; Xiao, Zhousheng; Xiong, Yuanyuan; Wang, Guangwei (Frontiers in Cell and Developmental Biology, 2020)
Osteoporosis is the most common age-related metabolic bone disease, which has been a major global health problem in elderly population. The balance between osteoblast-mediated bone formation and osteoclast-mediated bone resorption is the basis for maintaining bone health. Osterix (Osx) has long been known to be an essential transcription factor for the osteoblast differentiation and bone mineralization. Emerging evidence suggests that Osx not only plays an important role in intramembranous bone formation, but also affects endochondral ossification by participating in the terminal cartilage differentiation. Given its essentiality in skeletal development and bone formation, Osx has become a new research hotspot in recent years. In this review, we focus on the progress of Osx’s function and its regulation in osteoblast differentiation and bone mass. And the potential role of Osx in developing new therapeutic strategies for osteoporosis was discussed.